Antileukemic efficacy in vitro of talazoparib and APE1 inhibitor III combined with decitabine in myeloid malignancies - Samra, Vanessa; Flach, Johanna; Naumann, Nicole; Brendel, Susanne; Kleiner, Helga; Weiß, Christel; Seifarth, Wolfgang; Nowak, Daniel; Hofmann, Wolf-Karsten; Fabarius, Alice; Popp, Henning (Cancers, 2019)
Malignant hematopoietic cells of myelodysplastic syndromes (MDS)/chronic myelomonocytic leukemias (CMML) and acute myeloid leukemias (AML) may be vulnerable to inhibition of poly(ADP ribose) polymerase 1/2 (PARP1/2) and apurinic/apyrimidinic endonuclease 1 (APE1). PARP1/2 and APE1 are critical enzymes involved in single-strand break repair and base excision repair, respectively. Here, we investigated the cytotoxic efficacy of talazoparib and APE1 inhibitor III, inhibitors of PARP1/2 and APE1, in primary CD34+ MDS/CMML cell samples (n = 8; 4 MDS and 4 CMML) and in primary CD34+ or CD34− AML cell samples (n = 18) in comparison to healthy CD34+ donor cell samples (n = 8). Strikingly, talazoparib and APE1 inhibitor III demonstrated critical antileukemic efficacy in selected MDS/CMML and AML cell samples. Low doses of talazoparib and APE1 inhibitor III further increased the cytotoxic efficacy of decitabine in MDS/CMML and AML cells. Moreover, low doses of APE1 inhibitor III increased the cytotoxic efficacy of talazoparib in MDS/CMML and AML cells. In summary, talazoparib and APE1 inhibitor III demonstrated substantial antileukemic efficacy as single agents, in combination with decitabine, and combined with each other. Hence, our findings support further investigation of these agents in sophisticated clinical trials.
Gesehen am 06.12.2019